A sustained-release antibacterial impregnated adhesive, adhesive film paper, decorative panel and preparation method thereof

A synergistic method using melamine formaldehyde resin and Ag-MOF@CNF material in impregnated adhesive film paper provides sustained-release antibacterial properties, addressing low efficiency and durability issues of existing agents, achieving high antibacterial performance and industrial suitability.

CN116356608BActive Publication Date: 2024-12-20INST OF WOOD INDUDTRY CHINESE ACAD OF FORESTRY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310347200.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2024-12-20
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Existing antibacterial agents for impregnated paper rely on ultraviolet light irradiation, have low antibacterial efficiency, and poor durability, and there is a lack of sustained-release antibacterial solutions for impregnated film paper.

Method used

A method involving a specific proportion of melamine formaldehyde resin and Ag-MOF@CNF material is used to create a synergistic impregnating glue for impregnated adhesive film paper, which slowly releases silver ions for long-lasting antibacterial effects.

Benefits of technology

The impregnated adhesive film paper achieves excellent antibacterial performance against Escherichia coli and Staphylococcus aureus, meeting Grade I strong antibacterial standards with sustained release and minimal impact on resin properties, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116356608B_ABST
    Figure CN116356608B_ABST
Patent Text Reader

Abstract

The present invention relates to a slow-release antibacterial impregnated adhesive, adhesive film paper, decorative panel and a preparation method thereof. A mixed material of melamine formaldehyde resin and Ag-MOF@CNF is used as an impregnated adhesive, and the impregnated adhesive is impregnated on paper impregnated with urea-formaldehyde glue to obtain a slow-release antibacterial impregnated adhesive film paper; the impregnated adhesive film paper and plywood or blockboard are hot-pressed to obtain an impregnated adhesive film paper decorative panel. The obtained impregnated adhesive film paper or decorative panel has excellent antibacterial performance, can reach the grade I strong antibacterial grade standard, and has good durability and has no effect on the surface performance of paper / decorative panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wood processing, and in particular to a method for preparing an impregnated adhesive film paper and a decorative panel thereof. Background Art

[0002] Furniture and decorative materials that people frequently touch will retain a large number of harmful substances such as bacteria and fungi, and microorganisms are easy to attach, reproduce and spread on their surfaces, which can easily cause cross-infection. Consumers' requirements for indoor health have risen from the safety and environmental protection of raw materials to antibacterial properties.

[0003] Impregnated paper is made of special paper impregnated with amino resin or phenolic resin, dried to a certain degree of solidification, and can be bonded to each other or pasted on the surface of artificial boards through hot pressing. It is mainly used in furniture decoration, packaging and other industries, and plays an important role in people's work and living environment, but it is very easy to become a medium for the spread of pathogens, and it is urgent to carry out antibacterial treatment on impregnated paper.

[0004] In order to solve the problem of antibacterial of impregnated paper, CN210596830U proposed a method for preparing melamine impregnated paper by adding antibacterial nano zinc oxide into the melamine resin layer to obtain an antibacterial rate of 99% against Staphylococcus aureus and Escherichia coli. However, the antibacterial effect of photocatalytic antibacterial agents needs to rely on ultraviolet light irradiation, which limits their widespread use.

[0005] CN114318948B proposes to add 0.5-1% nano magnesium oxide to melamine formaldehyde resin glue, and obtain antibacterial melamine formaldehyde impregnated adhesive film paper through antibacterial impregnation, drying and hot pressing. However, nano magnesium oxide has poor antibacterial ability, low efficiency and short durability.

[0006] Metal organic frameworks (MOFs) are open crystal frameworks with stable porosity built by organic ligands and metal elements. So far, MOFs have been studied and confirmed to have sustained-release antibacterial properties. CN114634657A provides a Ag-MOF composite chitosan-based film and its preparation method and application. The obtained film material has good air permeability and bactericidal properties, and can be used as a sustained-release antibacterial food packaging material to extend the shelf life of food. Jaffres et al. reported a 3D Ag-MOF, which is composed of Ag + It is composed of 3-phosphonobenzoic acid with both carboxyl and phosphonic acid functional groups, and can effectively kill six bacteria including methicillin-resistant Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa through the long-term sustained release of Ag+. However, there are no reports on the application of Ag-MOF materials in impregnated film paper.

[0007] In view of this, the present application provides a method for preparing a highly efficient and durable antibacterial impregnated film paper to solve or at least alleviate the above technical defects. Summary of the invention

[0008] The purpose of the present invention is to solve the problems that the existing antibacterial agents for impregnated paper rely on ultraviolet light irradiation, have low antibacterial efficiency and poor durability, and to provide a method for preparing a sustained-release antibacterial impregnated adhesive film paper and a decorative panel thereof. The impregnated adhesive provided by the present invention adopts a specific proportion of melamine formaldehyde resin and a specific Ag-MOF@CNF material to work synergistically, has excellent antibacterial performance, and can effectively solve the technical problems of low antibacterial efficiency and poor durability of the existing antibacterial agents for impregnated paper.

[0009] In order to achieve the above object, the present invention provides an impregnation glue on one hand, wherein the impregnation glue comprises: 100 parts by weight of melamine formaldehyde resin and 0.05-0.3 parts by weight of Ag-MOF@CNF material.

[0010] Although the Ag ions in the Ag-MOF material themselves have a certain antibacterial effect, the inventors discovered during the research process that Ag-MOF can be used as a storage reservoir for metal ions in the melamine formaldehyde resin system. The silver ions with antibacterial function can be slowly released to achieve a long-lasting and efficient antibacterial effect, thereby further improving the antibacterial performance and having the advantage of low cost.

[0011] Preferably, the impregnating glue comprises: 100 parts by weight of melamine formaldehyde resin and 0.1-0.2 parts by weight of Ag-MOF@CNF material.

[0012] The weight average molecular weight of the melamine formaldehyde resin is 200-1000, preferably 400-600.

[0013] The Ag-MOF@CNF material is a white solid powder, containing three elements: carbon, oxygen and silver, wherein the percentage of silver atoms is 12%-14%.

[0014] The second aspect of the present invention provides a method for preparing impregnated glue-film paper, the method comprising: firstly impregnating raw paper in urea-formaldehyde resin impregnation liquid to obtain paper I, and then coating the impregnating glue described in the first aspect on paper I to obtain impregnated glue-film paper.

[0015] The third aspect of the present invention provides an impregnated adhesive film paper prepared by the preparation method described in the second aspect.

[0016] The fourth aspect of the present invention provides a method for preparing an impregnated film paper veneer, the method comprising: hot pressing the impregnated film paper described in the third aspect and a substrate, the substrate being plywood or blockboard, to obtain an impregnated film paper veneer.

[0017] Through the above technical solution, the beneficial effects of the present invention include:

[0018] 1) The impregnating glue provided by the present invention adopts a specific ratio of melamine formaldehyde resin and Ag-MOF@CNF material to work synergistically, and has excellent antibacterial properties, which can effectively solve the technical problems of low antibacterial efficiency, poor durability, easy discoloration, and dependence on ultraviolet light irradiation of existing antibacterial agents for impregnated paper.

[0019] 2) The antibacterial agent prepared by the present invention has good compatibility with MF resin and has little effect on the properties of MF resin (curing time, viscosity) and the surface properties of impregnated film paper (surface crack resistance, surface wear resistance, surface water vapor resistance).

[0020] 3) The impregnated adhesive film paper decorative panel provided by the present invention has good antibacterial activity against Escherichia coli and Staphylococcus aureus, and can reach the level I strong antibacterial grade standard.

[0021] 4) The preparation method of the impregnated adhesive film paper and the impregnated adhesive film paper veneer provided by the present invention is simple to operate, low in cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The Ag of the impregnated film paper obtained in Example 4 + Sustained release graph;

[0023] Figure 2 The Ag of the impregnated film paper obtained in Example 8 + Sustained release graph;

[0024] Figure 3 The Ag content of the impregnated film paper prepared in Example 2 is + Slow-release diagram. DETAILED DESCRIPTION

[0025] In one aspect, the present invention provides an impregnation adhesive, which comprises: 100 parts by weight of melamine formaldehyde resin and 0.05-0.3 parts by weight of Ag-MOF@CNF material.

[0026] Preferably, the impregnation glue comprises: 100 parts by weight of melamine formaldehyde resin and 0.1-0.2 parts by weight of Ag-MOF@CNF material. When the amount of Ag-MOF@CNF material added is less than 0.1 parts by weight, it will lead to poor antibacterial effect. When the amount of Ag-MOF@CNF material added is more than 0.2 parts by weight, it will lead to excessive oxidation reaction of silver ions after hot pressing, and the impregnated surface will appear yellow-brown, affecting the aesthetics of the impregnated paper.

[0027] The weight average molecular weight of the melamine formaldehyde resin is 200-1000, preferably 400-600. With this implementation, the curing time, viscosity and storage period of the MF resin are less affected, and in this case, the compatibility of the MF resin and the Ag-MOF@CNF material is good.

[0028] The Ag-MOF@CNF material is a white solid powder. Ag-MOF@CNF contains three elements: carbon, oxygen and silver, wherein the percentage of silver atoms is 12%-14%.

[0029] Furthermore, the preparation method of the Ag-MOF@CNF material comprises the following steps:

[0030] (1) mixing a phenyl ligand, water and an organic solvent to obtain a mixed solution;

[0031] (2) reacting the mixed solution obtained in step (1) with an aqueous solution of a silver soluble salt added with nanocellulose at 20-60° C., and then centrifuging and drying to obtain a dry Ag-MOF@CNF powder material.

[0032] In the present invention, in the mixing process of the phenyl ligand, water and organic solvent in step (1), the order of adding the materials is not particularly limited. The materials can be added together, or two of the components can be mixed and then the remaining components can be added in sequence. In order to enhance the mixing uniformity, preferably, the mixing in step (2) includes: first mixing water and the organic solvent, and then mixing with the phenyl ligand for a second time to obtain a mixed solution.

[0033] According to the present invention, preferably, the mixing in step (2) is performed under ultrasonic conditions. The present invention has no particular limitation on the specific conditions of the ultrasonic conditions, which can be appropriately selected according to the specific circumstances, as long as the purpose of uniform mixing can be achieved.

[0034] According to the present invention, preferably, the volume ratio of water to organic solvent is 1:0.5-1.5, preferably 1:0.8-1.2.

[0035] According to the present invention, preferably, in the mixed solution of step (1), the concentration of the phenyl ligand is 5-9 g / L, preferably 6.5-7.5 g / L.

[0036] The phenyl ligand of the present invention is a common rigid carboxylic acid ligand with good thermal stability, and carboxylic acid MOFs usually have a large specific surface area and regular pores, and the high specific surface area and high porosity of carboxylic acid MOFs can increase the content of silver ions in three-dimensional space, and achieve the slow release of metal ions, making the antibacterial effect more durable. According to the present invention, preferably, the phenyl ligand is selected from at least one of trimesic acid, pyromellitic acid and terephthalic acid, preferably trimesic acid. Trimellitic acid contains three carboxyl groups, has strong coordination ability, diverse patterns, mild reaction conditions and high yield.

[0037] The present invention has a wide range of choices for the organic solvent, and can be various solvents commonly used in the art. Preferably, the organic solvent is selected from at least one of ethanol, methanol and dimethylformamide, and is preferably ethanol for economic considerations.

[0038] According to the present invention, preferably, the concentration of the aqueous solution of the soluble silver salt is 1-3 g / L, preferably 1.5-2.5 g / L.

[0039] The present invention has a wide range of selection for the type of the soluble silver salt. Preferably, the soluble silver salt is AgNO3.

[0040] According to the present invention, preferably, the reaction conditions of step (2) include: the temperature is preferably 20-40°C; the reaction time is 1-3h, preferably 1.5-2.5h. With this preferred embodiment, the reaction time is short, the reaction temperature is not high, the yield is high, and the solvent is green.

[0041] According to the present invention, preferably, the amount of the mixed solution obtained in step (2) is 20-50 parts by volume, preferably 30-40 parts by volume, relative to 100 parts by volume of the nanocellulose (CNF) aqueous solution of AgNO3. By adopting this preferred embodiment, the relatively expensive AgNO3 can be fully reacted, thereby reducing the production cost of the Ag-MOF@CNF material.

[0042] As long as the preparation method of the melamine formaldehyde resin having the above-mentioned weight average molecular weight can be prepared, the purpose of the present invention can be achieved. The present invention has no particular limitation on the preparation method of the melamine formaldehyde resin. A specific preparation method is now provided, but the present invention is not limited thereto.

[0043] Preferably, the preparation method of the melamine formaldehyde resin comprises: subjecting a mixture of melamine, formaldehyde solution and distilled water to a prepolymerization reaction under condensation reflux conditions, controlling the pH value of the mixture to 8.5-9, reacting at 90-95° C. until the water solubility is 2-4, and then completing the reaction to obtain melamine formaldehyde resin (MF resin).

[0044] Preferably, the prepolymerization reaction is carried out under stirring conditions. The present invention has no particular limitation on the specific stirring conditions, which can be appropriately selected according to specific circumstances.

[0045] Preferably, the molar ratio of formaldehyde to melamine is 2-3.

[0046] The water solubility ratio of the present invention refers to the volume ratio of distilled water to the volume ratio of MF resin at 25° C. Formaldehyde and urea are both water-soluble substances. During the acidic reaction, as the reaction proceeds, the hydroxymethyl compounds polymerize to generate insoluble fusible compounds. Therefore, water miscibility reflects the reaction degree of the resin to a certain extent, which is of great significance.

[0047] The water solubility of the present invention is determined by the turbidity point method. The specific method is to use a 100mL cylinder to measure about 10mL of the MF resin to be tested (accurate to 0.1mL), and use a thermometer to confirm that the temperature of the MF resin and the temperature of the distilled water are (23±0.5℃). Use a burette to add distilled water dropwise to the resin and stir the resin. First, add about 50% of the amount of distilled water required to reach the miscibility limit, then add 30% of the amount of distilled water, and then add distilled water dropwise until the mixed solution turns white.

[0048] Preferably, the pH of the mixed material is adjusted using alkali.

[0049] The present invention has a wide range of selections for the type of the base, and various bases commonly used in the art can be used, and the present invention is not limited here.

[0050] The present invention does not specifically limit the preparation method of the impregnating glue. The impregnating glue can be obtained by mixing melamine formaldehyde resin and Ag-MOF material according to conventional operations in the art.

[0051] The second aspect of the present invention provides a method for preparing impregnated glue-film paper, the method comprising: firstly impregnating raw paper in urea-formaldehyde resin impregnation liquid to obtain paper I, and then coating the impregnating glue described in the first aspect on paper I to obtain impregnated glue-film paper.

[0052] The present invention does not impose any special limitation on the raw material paper, and any raw material paper commonly used in the art can be used in the present invention.

[0053] The present invention has a wide selection range for the urea-formaldehyde resin impregnation liquid, which can be a conventional choice in the art. Preferably, the urea-formaldehyde resin impregnation liquid comprises urea-formaldehyde resin and water, wherein the mass content of urea-formaldehyde resin is 45-65wt%, preferably 55-60wt%.

[0054] Preferably, the weight average molecular weight of the urea-formaldehyde resin is 600-1000, preferably 700-900.

[0055] According to the present invention, preferably, the impregnation conditions include: an impregnation temperature of 20-30° C. and an impregnation time of 40-50 s.

[0056] According to the present invention, preferably, the method further comprises: subjecting the impregnated raw paper to a first drying to obtain paper I.

[0057] According to the present invention, preferably, the first drying conditions include: temperature of 90-110° C., and time of 2-3 min.

[0058] According to the present invention, preferably, the impregnation amount of urea-formaldehyde resin on the paper I is 80-120 g / m 2 , preferably 90-110g / m 2 The use of this preferred embodiment can reduce production costs. Urea-formaldehyde resin has good permeability and can better complete the substrate impregnation. Good substrate impregnation is one of the necessary conditions for the excellent surface performance of the impregnated film paper veneer.

[0059] In the present invention, the impregnation amount refers to the mass difference per unit area between the paper I and the raw material paper.

[0060] The present invention does not impose any particular limitation on the specific conditions of the coating, and the coating may be performed according to conventional operations in the art.

[0061] According to the present invention, the method further comprises: performing a second drying on the coated paper I to obtain impregnated glue film paper.

[0062] According to the present invention, the second drying conditions include: temperature of 110-130° C. and time of 2-3 min.

[0063] According to the present invention, the coating amount of the impregnated adhesive on the impregnated adhesive film paper is 30-70g / m 2 , preferably 40-60g / m 2 By adopting this preferred embodiment, the MF resin can be uniformly adhered to the top and bottom of the paper I without penetrating into the inside of the base paper, and the impregnated paper is not prone to warping and deformation.

[0064] In the present invention, the coating amount refers to the mass difference between the impregnated glue-film paper and the paper I per unit area.

[0065] The third aspect of the present invention provides an impregnated adhesive film paper prepared by the preparation method described in the second aspect.

[0066] The fourth aspect of the present invention provides a method for preparing an impregnated film paper veneer, the method comprising: hot pressing the impregnated film paper of the third aspect and a substrate, wherein the substrate is plywood or blockboard, to obtain the impregnated film paper veneer.

[0067] The present invention does not impose any special limitation on the plywood and / or blockboard, and any plywood or blockboard commonly used in the art may be selected.

[0068] According to the present invention, preferably, the hot pressing conditions include: hot pressing pressure of 0.5-6MPa, preferably 1-3MPa; hot pressing temperature of 110-130°C, preferably 110-120°C; hot pressing time of 3-10min, preferably 5-7min.

[0069] The present invention will be described in detail below through examples.

[0070] The reagents used in the following examples are commercially available and of analytical grade.

[0071] Preparation Examples I-1 to I-2 are used to illustrate the preparation of Ag-MOF@CNF materials

[0072] Preparation Example I-1

[0073] The TEMPO-oxidized nanocellulose CNF (solid content 1.2%) was dissolved in distilled water at room temperature and ultrasonically treated in cold water for 30 minutes to obtain a CNF aqueous solution (containing CNF 1g / L). AgNO3 (purity 99.0%) was dissolved in distilled water at room temperature to obtain an AgNO3 aqueous solution (containing silver nitrate 2g / L). 5mL of CNF aqueous solution was added to 50mL of AgNO3 aqueous solution and reacted at room temperature for 30min to obtain an AgNO3 CNF aqueous solution. H3BTC was dissolved in a mixed solution of water and ethanol (the volume ratio of water to ethanol was 1:1) under ultrasonic treatment (containing H3BTC 7g / L) to obtain a mixed solution of H3BTC. Finally, the mixed solution of H3BTC (20mL) was added dropwise to the mixed solution of CNF of AgNO3 and reacted at room temperature for 2h. Then centrifugation and drying were performed to obtain a white solid powder Ag-MOF@CNF-25.

[0074] Preparation Example I-2

[0075] The only difference from Preparation Example I-1 is that the last step is to react at 60°C for 2h. Then centrifugation and drying are performed to obtain white solid powder Ag-MOF@CNF-60.

[0076] Preparation Example I-3

[0077] AgNO3 (purity of 99.0%) was dissolved in distilled water at room temperature to obtain an AgNO3 aqueous solution (containing 2 g / L silver nitrate), and H3BTC was dissolved in a mixed solution of water and ethanol (the volume ratio of water to ethanol was 1:1) (containing 7 g / L H3BTC) under ultrasonic treatment to obtain a mixed solution of H3BTC. 20 mL of the mixed solution of H3BTC was added dropwise to 50 mL of the AgNO3 aqueous solution, and then reacted at room temperature for 2 h, and then centrifuged and dried to obtain white crystalline powder Ag-MOF.

[0078] Preparation Example II-1

[0079] This preparation example is used to illustrate the preparation of melamine formaldehyde resin

[0080] Formaldehyde, melamine and distilled water are added into a three-necked flask equipped with a condensation reflux device and a stirring device, the molar ratio of formaldehyde to melamine is 2:1, and then the pH value is adjusted to 9 with a NaOH solution, and the reaction is completed at 90° C. when the water-soluble multiple is 3, to obtain a melamine formaldehyde resin with a weight average molecular weight of 500.

[0081] Example 1

[0082] (1) Add the white solid powder Ag-MOF@CNF-25 prepared in Preparation Example I-1 to the melamine formaldehyde resin prepared in Preparation Example II-1, with the added amount being 0.05% (mass ratio) of the melamine formaldehyde resin, and stir to mix to obtain an impregnated adhesive.

[0083] (2) At room temperature, the raw paper was immersed in a urea-formaldehyde resin aqueous solution (the weight average molecular weight of the urea-formaldehyde resin was 900 and the mass content was 55%) for 45 seconds, then taken out and dried at 110° C. for 3 minutes to obtain paper I; wherein the amount of urea-formaldehyde resin impregnated on paper I was 110 g / m 2 Then, the impregnated adhesive obtained in step (1) is evenly coated on the paper I through a rubber roller, and dried at 110°C for 2 minutes to obtain an impregnated adhesive film paper; wherein the coating amount of the impregnated adhesive on the impregnated adhesive film paper is 50g / m 2 .

[0084] (3) The impregnated adhesive film paper is placed on a blockboard and pressed at 120° C. and 0.7 MPa for 7 min to obtain an impregnated paper veneer artificial board.

[0085] Example 2

[0086] The method of Example 1 was followed, except that in step (1), the amount of Ag-MOF@CNF-25 added was 0.1% (mass ratio) of the melamine formaldehyde resin.

[0087] Example 3

[0088] The method of Example 1 was followed, except that in step (1), the amount of Ag-MOF@CNF-25 added was 0.2% (mass ratio) of the melamine formaldehyde resin.

[0089] Example 4

[0090] The method of Example 1 was followed, except that in step (1), the amount of Ag-MOF@CNF-25 added was 0.3% (mass ratio) of the melamine formaldehyde resin.

[0091] Example 5

[0092] (1) Add the white solid powder Ag-MOF@CNF-60 prepared in Preparation Example I-2 to the melamine formaldehyde resin prepared in Preparation Example II-1, with the added amount being 0.05% (mass ratio) of the melamine formaldehyde resin, and stir to obtain an impregnated adhesive.

[0093] (2) At room temperature, the raw paper was immersed in a urea-formaldehyde resin aqueous solution (the weight average molecular weight of the urea-formaldehyde resin was 900 and the mass content was 55%) for 45 seconds, then taken out and dried at 110° C. for 3 minutes to obtain paper I; wherein the amount of urea-formaldehyde resin impregnated on paper I was 110 g / m 2 The impregnated adhesive obtained in step (1) is evenly coated on the surface of paper I through a rubber roller, dried at 110°C for 2 minutes, and cooled to obtain impregnated adhesive film paper; wherein the coating amount on the impregnated adhesive film paper is 50g / m 2 .

[0094] (3) The impregnated adhesive film paper is placed on a blockboard and pressed at 120° C. and 0.7 MPa for 7 min to obtain an impregnated paper veneer artificial board.

[0095] Example 6

[0096] The method of Example 5 was followed, except that in step (1), the amount of Ag-MOF@CNF-60 added was 0.1% (mass ratio) of the melamine formaldehyde resin.

[0097] Example 7

[0098] The method of Example 5 was followed, except that in step (1), the amount of Ag-MOF@CNF-60 added was 0.2% (mass ratio) of the melamine formaldehyde resin.

[0099] Example 8

[0100] The method of Example 5 was followed, except that in step (1), the amount of Ag-MOF@CNF-60 added was 0.3% (mass ratio) of the melamine formaldehyde resin.

[0101] Comparative Example 1

[0102] The difference from Example 1 is that Ag-MOF@CNF-25 is not added.

[0103] Comparative Example 2

[0104] The difference from Example 1 is that the dried Ag-MOF solid prepared in Preparation Example I-3 is added to the melamine formaldehyde resin prepared in Preparation Example II-1, and the added amount is 0.3% (mass ratio) of the melamine formaldehyde resin, and the mixture is stirred and mixed to obtain the impregnation glue.

[0105] Comparative Example 3

[0106] The method of Example 2 is followed, except that the weight average molecular weight of the melamine formaldehyde resin is 200.

[0107] Comparative Example 4

[0108] The method of Example 2 was followed, except that the weight average molecular weight of the melamine formaldehyde resin was adjusted to 1000.

[0109] Test Example 1

[0110] The impregnated paper veneer blockboards prepared in the examples and comparative examples were subjected to antibacterial tests, and the specific test method was carried out in accordance with LY / T1926-2020 "Testing and grading of antibacterial properties of artificial boards and wood (bamboo) products". The test results are shown in Table 1.

[0111] Table 1

[0112]

[0113] It can be seen from the results in Table 1 that the impregnated paper facing blockboard prepared by using the impregnated adhesive of the present invention has good antibacterial activity against both Escherichia coli and Staphylococcus aureus, and can reach the Grade I strong antibacterial grade standard.

[0114] Test Example 2

[0115] The antibacterial effect of the impregnated film paper of the present invention is mainly achieved by the release of silver ions. Since the sustained release performance of silver ions in Ag-MOF@CNF is independent of the content of Ag-MOF@CNF, the Ag content of the supernatant of the impregnated film paper prepared in Example 4, Example 8 and Comparative Example 2 after soaking in water is calculated. + The release concentration was measured to verify the sustained-release performance of the impregnated film paper, and repeated immersion was used to verify the repeatability of the sustained-release performance.

[0116] The impregnated paper veneer blockboard samples prepared in Example 4, Example 8 and Comparative Example 2 after hot pressing, with a size of 75 mm*150 mm, were immersed in 100 mL of distilled water, and the supernatant was taken at different times (1, 2, 3, 4, 5, 6 h) to measure the silver ion concentration. In order to prove the repeatability of the sustained release performance, the impregnated film paper was immersed for multiple times and the Ag ion concentration was measured. + The trend of release. + The concentration was determined by inductively coupled plasma mass spectrometry (ICP-MS, PerkinElmer ICPMS NexlON300D, USA). Figure 1-3 shown.

[0117] pass Figure 1-3 It can be seen that the impregnated paper prepared by the impregnated adhesive of the present invention has good sustained release performance, and the sustained release performance of the impregnated paper after immersion for 4 times is not weakened, indicating that Ag can be released efficiently and persistently. + It can be seen that the impregnated film paper prepared by the impregnated adhesive of the present invention achieves a highly efficient and long-lasting antibacterial effect of the antibacterial agent Ag-MOF@CNF at a low addition amount.

[0118] Test Example 3

[0119] The dipping glues prepared in Example 4, Example 8 and Comparative Examples 1 and 2 were tested for 4-cup viscosity. The 4-cup viscosity was tested in accordance with GB / T 1723-93 "Paint Viscosity Test Method", and the test results are shown in Table 2.

[0120] Table 2

[0121]

[0122] From the results in Table 2, it can be seen that the Ag-MOF@CNF with CNF added has little effect on the viscosity of the MF resin and meets the requirements of the MF resin for impregnation. However, the Ag-MOF powder without CNF added has a greater effect on the viscosity of the MF resin and does not meet the requirements of the MF resin for impregnation.

[0123] Test Example 4

[0124] The curing time of the impregnated adhesives prepared in the examples and comparative examples was measured. The curing time was measured in accordance with GB / T14074-2017 "Test Methods for Adhesives and Resins for Wood Industry", and the test results are shown in Table 3.

[0125] Table 3

[0126] Example No. Curing time (min) Comparative Example 1 6.10 Example 1 6.05 Example 2 6.07 Example 3 6.15 Example 4 6.08 Example 5 6.05 Example 6 6.08 Example 7 6.07 Example 8 6.12 Comparative Example 2 5.12

[0127] From the results in Table 3, it can be seen that the addition of CNF-added Ag-MOF@CNF has little effect on the curing time of MF resin, which can be ignored and meets the requirements of MF resin for impregnation. However, Ag-MOF powder without CNF addition has a greater effect on the curing time of MF resin and does not meet the requirements of MF resin for impregnation.

[0128] It should be noted that, from Test Examples 3-4, it can be seen that the impregnated glue used in combination with the specific ratio of Ag-MOF@CNF and MF resin in the present invention not only meets the requirements of antibacterial performance, but is obtained after considering many factors.

[0129] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a sustained-release antibacterial impregnated film paper, characterized in that: The method comprises: firstly, impregnating raw paper in urea-formaldehyde resin impregnation liquid to obtain paper I, and then coating the impregnating glue on the paper I to obtain impregnated glue film paper; The impregnation glue is composed of 100 parts by weight of melamine formaldehyde resin and 0.05-0.3 parts by weight of Ag-MOF@CNF material; the weight average molecular weight of the melamine formaldehyde resin is 200-1000; The preparation method of the Ag-MOF@CNF material comprises the following steps: (1) dissolving AgNO3 in distilled water at room temperature to obtain an AgNO3 aqueous solution with a concentration of 1-3 g / L, adding a nanocellulose CNF aqueous solution with a concentration of 0.5-2 g / L to the AgNO3 aqueous solution and reacting at 20-40° C. for 20-40 min to obtain an AgNO3 CNF aqueous solution; the amount of the CNF aqueous solution used is 5-15 parts by volume relative to 100 parts by volume of the AgNO3 aqueous solution; (2) firstly mixing water and an organic solvent, and then secondly mixing with a phenyl ligand to obtain a mixed solution; the phenyl ligand is selected from at least one of trimesic acid, pyromellitic acid and terephthalic acid; and the concentration of the phenyl ligand is 5-9 g / L; (3) reacting the mixed solution obtained in step (2) with the CNF aqueous solution containing AgNO3 obtained in step (1) at 20-60°C for 1-3h, and then centrifuging and drying to obtain Ag-MOF@CNF material.

2. The method for preparing the sustained-release antibacterial impregnated film paper according to claim 1, characterized in that: The impregnating glue comprises: 100 parts by weight of melamine formaldehyde resin and 0.1-0.2 parts by weight of Ag-MOF@CNF material.

3. The method for preparing the sustained-release antibacterial impregnated film paper according to claim 1, characterized in that: In the step (1), the amount of CNF aqueous solution is 8-12 parts by volume relative to 100 parts by volume of AgNO3 aqueous solution; in the step (2), the organic solvent is selected from at least one of ethanol, methanol and dimethylformamide; the volume ratio of water to organic solvent is 1:0.5-1.5; the concentration of the phenyl ligand is 6.5-7.5 g / L; in the step (3), the reaction conditions are: temperature is 20-40°C, and reaction time is 1.5-2.5h.

4. The method for preparing the sustained-release antibacterial impregnated film paper according to claim 3, characterized in that: The volume ratio of water to organic solvent is 1:0.8-1.

2.

5. The method for preparing the sustained-release antibacterial impregnated film paper according to claim 1, characterized in that: The urea-formaldehyde resin impregnation liquid comprises urea-formaldehyde resin and water, wherein the mass content of the urea-formaldehyde resin is 45-65wt%; the impregnation conditions include: an impregnation temperature of 30-60°C and an impregnation time of 40-50s.

6. The method for preparing the sustained-release antibacterial impregnated film paper according to claim 5, characterized in that: The mass content of the urea-formaldehyde resin is 55-60wt%.

7. The method for preparing the sustained-release antibacterial impregnated film paper according to any one of claims 1 to 6, characterized in that: The method further comprises: performing a first drying on the impregnated raw paper to obtain paper I; the conditions of the first drying include: a temperature of 90-110° C. and a time of 2-3 min; the impregnation amount of urea-formaldehyde resin on the paper I is 80-120 g / m 2 .

8. The method for preparing the sustained-release antibacterial impregnated film paper according to any one of claims 1 to 6, characterized in that: The method further comprises: performing a second drying on the coated paper I to obtain impregnated glue film paper; The second drying conditions include: temperature of 110-130°C and time of 2-3 minutes; The coating amount of the impregnated glue on the impregnated glue film paper is 30-70g / m 2 .

9. An impregnated film paper prepared by the method for preparing the sustained-release antibacterial impregnated film paper according to any one of claims 1 to 6.

10. A method for preparing a sustained-release antibacterial impregnated film paper veneer, characterized in that: The method comprises: hot pressing the impregnated film paper of claim 9 and a substrate, wherein the substrate is plywood or blockboard, to obtain an impregnated film paper veneer; the hot pressing conditions comprise: a hot pressing pressure of 0.5-6MPa; a hot pressing temperature of 110-130°C; and a hot pressing time of 3-10min.

Citation Information

Cited By

  • Preparation method of antibacterial functional compound with stable structure, impregnation liquid, impregnated paper and veneer

    CN122105907A